Calculus 10th Edition

Published by Brooks Cole

Chapter 6 - Differential Equations - 6.1 Exercises: 6

Answer

It is a solution of the differential equation.

Work Step by Step

Find the first and second derivatives. $y=C_1 e^{-x} cos{x} + C_2 e^{-x} sin{x}$ $y= e^{-x}(C_1cos(x) +C_2 sin(x))$ $y'= -e^{-x} ( C_1cos(x) + C_2 sin(x) ) + e^{-x} (-C_1 sin(x) +C_2 cos(x))$ $y'= e^{-x} [(C_2 -C_1)cos(x) - (C_1+C_2)sin(x)]$ $y''= -e^{-x}[(C_2-C_1)cos(x) - (C_1+C_2) sin(x)] + e^{-x}[-(C_2 - C_1)sin(x) - (C_1 + C_2) cos(x)]$ $y''= 2e^{-x}(C_1 sin(x) - C_2cos(x))$ Plug back into the differential equation $2e^{-x}((C_1 sin(x) - C_2cos(x)) + 2e^{-x} [(C_2 -C_1)cos(x) - (C_1+C_2)sin(x)] + 2e^{-x}(C_1cos(x) +C_2 sin(x)) =0$ Simplify $2e^{-x}(C_1sin(x) -C_2cos(x) +C_2cos(x) -C_1 cos(x) -C_1sin(x) -C_2sin(x) + C_1cos(x) +C_2sin(x))= 0$ All terms cancel out and $0=0$ So, it is a solution to the differential equation.

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.